Análisis de factibilidad para la producción de melón honeydew en el cantón Arenillas para su exportación - Carrillo Torres, Carlos Rodrigo (2014)
This study's main objective was to determine the feasibility of producing honeydew in canton Arenillas to export to the United States market as an alternative production in this county, showing that there is a viable market as international consumption level is growing, the US being one of the main consumers of this product, although it was verified that the domestic market is satisfied, wich an economic analysis where showed earnings that would be generated at the end of production took place, as revenues were above expenditures and percentages in the financial analysis validated that the project is feasible, for it was obtained to study the market variables, technical requirements and economic variables to the merits of the work, where the current market melon is completely unsatisfied because since 2007 have remained imports from Colombia and Peru, but have remained steady exports to European markets, technical survey activities that must be performed which showed no are impediments to make the crop.